Primary health care for noncommunicable diseases in the Philippines - Valerie Gilbert T. UIep; Jhanna Uy; Lyle Daryll Casas (Philippine Institute for Development Studies (PIDS), 2020)
Noncommunicable diseases (NCDs) have become the major cause of disease burden in the Philippines. In 2019, NCDs accounted for about 70 percent of the 600,000 deaths nationwide; this is projected to increase in the medium to long term. The premature deaths due to NCDs are increasing in a much faster rate in poorest communities while declining in relatively rich areas. The growing burden of NCDs in poor communities have implications on the poverty reduction efforts and economic prospects of the country. Despite the growing threat of NCDs, the Philippine health system remains historically designed and oriented to address infectious diseases and maternal and child health. This has led to episodic and fragmented delivery of health services–a model that has difficulty handling NCDs. As the country embarks to institute major reforms in the Universal Health Care Act towards a primary health care-oriented and integrated health system, this study will identify the specific challenges in governance, financing, service delivery, and health human resources that hinder the realization of comprehensive and continuous delivery of NCD services in local communities.
Keywords: 330; non-communicable diseases; primary health care; health systems